Fault Diagnosis of Automobile Crane Power Steering System Aided by ICP-AES - Lidan Chen (Institute of Advanced Engineering and Science, 2013)
The objective of this paper is to evaluate an innovative application of inductively coupled plasma atomic emission spectroscopy (ICP-AES) on the fault diagnosis of automobile crane hydraulic power steering (HPS) system. Contents of Fe, Cu and Al were examined by ICP-AES in the oil samples of HPS system for four different mileages of Puyuan QY50H. The mileages were 2000-9000 km, 11000-19000 km, 21000-28000 km and 32000-40000 km separately. Database of major mental contents in automobile crane HPS system of Puyuan QY50H with different mileage were calibrated. Results showed that, major mental contents were increased with the increasing of driving mileage and the normal contents laid between two trend lines. Through the determination of mental contents in HPS oil sample and further compared them with the values in their database, we could not only evaluate the wear condition of automobile crane HPS system, but also helped to diagnose the faults without dissembled the problematic vehicle. The results further indicated that, in time maintenance, high quality and low cost reparation could be realized by the application of ICP-AES technology on fault diagnosis of automobile crane power steering system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2214